Effect of Corn Oil on the Quality and Storage Stability of Pickled Fish - Behanan, Lizy; Mathew, Saleena; D., Sudharma; M.K., Mukundan; V., Malika (Fishery Technology, 2025)
The results of preparing lish pickles using corn oil and gingili oil are reported. Results showed that the pickle made using corn oil and acetic acid was superior in keeping quality, taste and texture than the pickle prepared using gingili oil and acetic acid. In addition the production of alpha amino nitrogen and free fatty acid during storage was found to be much less in corn oil and acetic acid treated piclde.